0.3(x-9)=0.6(2x+6)

Simple and best practice solution for 0.3(x-9)=0.6(2x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.3(x-9)=0.6(2x+6) equation:



0.3(x-9)=0.6(2x+6)
We move all terms to the left:
0.3(x-9)-(0.6(2x+6))=0
We multiply parentheses
0.3x-(0.6(2x+6))-2.7=0
We calculate terms in parentheses: -(0.6(2x+6)), so:
0.6(2x+6)
We multiply parentheses
1.2x+3.6
Back to the equation:
-(1.2x+3.6)
We get rid of parentheses
0.3x-1.2x-3.6-2.7=0
We add all the numbers together, and all the variables
-0.9x-6.3=0
We move all terms containing x to the left, all other terms to the right
-0.9x=6.3
x=6.3/-0.9
x=-7

See similar equations:

| 6(r+8)=-4(r-7) | | 12w=864 | | 6+3n=40 | | 4,-1+3y=6 | | c/4+1=10 | | 4p=9=-2p+21 | | 2x=x*31 | | -12x-4=176 | | 10+2v=-8v-10 | | 3n-6=40 | | –4=2p–6 | | 9+h=-9-5h | | 9(n-6)=162 | | 5+2/3x=-4+20 | | 6-3n=40 | | u/26=21 | | 2/5x-1=9;x= | | 3(5k+1)=k+17 | | Y+x=4x+16 | | 1=11x−9° | | 2.5-6.2r=5.8+0.4r | | 3y=-9+1 | | q+5/2=-1 | | -3(3x+4)+6x-21=-147 | | -4(2x–1)=-12 | | 8k-7=9+10k | | x^2+120-22x=0 | | 3x+26=-2x+6 | | -4=2(s+10)-4 | | (4a+50)=(7a-4) | | -3t=-2.1 | | z+–18=–3 |

Equations solver categories